Strain Imaging in Aortic Regurgitation - Manivasagam Raja Gopal; M Bharathkumaran (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2023)
Two-dimensional strain imaging has an established role in the detection of subtle or subclinical left ventricular (LV) dysfunction in cardiomyopathies. The application of strain imaging, particularly longitudinal strain (LS), is emerging as a simple yet powerful tool in the detection of the early decline of LV function in valvular heart diseases also, including aortic regurgitation (AR). The advantages of strain imaging include its simplicity of the concept and imaging technique, its rapidity, and less interpersonal variability. The detection of lower strain values may help the clinician to optimally time the surgical intervention among asymptomatic individuals with preserved ejection fraction (EF). Such a preemptive approach is expected to improve the surgical results and offer better outcomes in terms of longevity and reverse remodeling of LV. Numerous studies have confirmed that a global LS value of 19.5% is the ideal cutoff for the detection of early LV dysfunction in AR. It has been shown in studies that a decreased strain correlates with mortality in medically treated as well as in operated patients. Apart from being potentially helpful in the timing of surgery in asymptomatic individuals, the estimation of strain is also useful in the detection of the contractile reserve, which is translated into better postoperative outcomes. If this finding is supported by future studies, strain imaging may eventually replace stress echocardiography in evaluating asymptomatic patients with valve diseases. Even in patients with advanced disease and low EF, strain values are helpful in identifying the subset of individuals who show better response to surgery. A cutoff of 12% appears to be useful in the detection of responders in this high-risk group. The usefulness of radial and circumferential strain, apical and basal rotation, and layered strain remains to be established. The extension of strain measurements in assessing myocardial work appears to be an attractive option for assessing LV function without load dependency.